The Andalus historiographers role in the Orient at the Ayyubid Age - صارم, وفاء; مهنا, أسامة; رجب, وائل (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research was conducted to the Andalusian historiographers role who came to the Islamic Arabic Orient in development the historical authorship movement at the Ayyubid Age, by cognition the Stature that enjoys by Andalusian historians among the Ayyubid rulers and kings , and study major of historiographers in Al Andalus who departed to the Islamic Arabic Orient at the Ayyubid Age, (the traveler Ibn Jubair al-Kanani al-Andalusi, Ibn Dihya al-Kalbi and Ibn Said al-Maghrabi), and observation of their writing that they have left in different fields studying the method that each of those historians followed, and the effect that caused on development history in this important period of the Arabic Islamic History. The research also study impact of relationship between the Andalusian historiographers who came to the Islamic Arabic Orient and Ayyubid regnant authority on historical authorship movement and on the approach of those historians in the historical authorship in terms of credibility and objectivity on the one hand, and in terms of access to official documents of the State that help them to present the facts as they are on the other hand.